2019
DOI: 10.1088/1755-1315/333/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Wooden breast – a novel myopathy recognized in broiler chickens

Abstract: Abnormally hard breast fillet consistency began to emerge in commercial broiler chickens around 2010. Due to the remarkable muscle hardness, the condition acquired the vernacular name ‘wooden breast myopathy’. This myopathy starts to develop after two weeks of age at the earliest and typically proceeds into chronic myodegeneration in three to four weeks of age. The lesion begins focally and typically develops into a diffuse lesion that involves the entire major pectoral muscle. The restricted location of woode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Woody breast ( WB ) starts developing in broilers at as early as 2 wk of age. A chronic myodegradation may appear at 3 to 4 wk of age ( Baltic et al., 2019 ). According to Sihvo et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Woody breast ( WB ) starts developing in broilers at as early as 2 wk of age. A chronic myodegradation may appear at 3 to 4 wk of age ( Baltic et al., 2019 ). According to Sihvo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors affect the development of WB, including the broiler's genotype, gender, egg incubation condition, diet, and feeding allocation ( Tijare et al., 2016 ; Bowker and Zhuang, 2017 ; Meloche et al., 2018 ; Zhang et al., 2020a ; Oviedo-Rondón et al., 2020 ). One factor that has been consistently associated with the incidence of WB is heavier body weight and thicker fillets ( Trocino et al., 2015 ; Baltic et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lesions in poultry meat have led to economic losses within the industry, especially due to WS and WB (Huang & Ahn 2018, Zanetti et al 2018. Once WS and WB impair the appearance and functional quality of breast meat (Huang & Ahn 2018), affected breast fillets are often downgraded and sold at a discount, used for further processing, or even discarded (Baltic et al 2019). The notable discolorations on the skin-side surfaces of severe WB fillets after cooking and the white striations on the ventral surfaces of raw WS fillets negatively impacts the purchasing decisions of consumers (Huang & Ahn 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Histology observation showed the main characteristics of WB as necrosis and fibrosis, connective tissue infiltration, lipid infiltration, fiber diameter increase, fiber degeneration and regeneration, and inflammatory cell infiltration [ 12 , 15 , 16 ]. Analysis of meat quality found that shear force and compression force in WB are significantly higher than those in the normal breast (NB) [ 14 , 17 ], thus causing low consumer acceptance and economic loss. Xing [ 18 ] surveyed the incidence of WB in China, and the proportion was approximately 61.9%.…”
Section: Introductionmentioning
confidence: 99%